WOMEN’S STRUGGLE AGAINST OPPRESSIONS IN “THE CASE OF THE MISSING MARQUESS” BY NANCY SPRINGER - Griselda Giovanni Simanjuntak; Tomi Arianto (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
The Victorian era was closely related to the patriarchal system. During this era, many women were oppressed because their activities were so restricted. The women during the Victorian era were not brave enough to fight but Enola Holmes was the only exception. Enola was portrayed as a brave young girl who fought for the patriarchal system in order to gain her freedom as a woman. The approach of this research is feminism approach which is explained by the theory of Sara Ahmed (2017). This research is designed with the descriptive qualitative method because the data source is taken from a novel entitled “The Case of the Missing Marquess” by Nancy Springer. The first aim of this research is to find out the main character’s oppressions toward the patriarchal system and the second aim is to reveal how the main character struggles against the patriarchal system during the Victorian era in the novel. (1) The first result of this research shows that there are eight data that have been found to answer the oppressions toward the main character and (2) the second result of this research shows that there are five data that have been found to answer how the main character struggles against the patriarchal system. To sum up, there are oppressions and there are struggles against the patriarchal system in the Victorian era portrayed by the main character.